Percutaneous Compression Plate versus Dynamic Hip Screw for Treatment of Intertrochanteric Hip Fractures: A Meta-Analyse of Five Randomized Controlled Trials - Lei Zhang; Jie Shen; Shengpeng Yu; Qiang Huang; Zhao Xie (The Scientific World Journal)
Background. Percutaneous compression plating (PCCP) has been advocated to reduce blood loss, relieve pain, and lead to faster rehabilitation for the treatment of intertrochanteric fractures. The purpose of this meta-analysis was to estimate the outcomes and complications of the PCCP versus dynamic hip screw (DHS) fixation for intertrochanteric fractures. Methods. All randomized controlled trials (RCT) that compared PCCP with DHS in treating adult patients with intertrochanteric fractures were included. Main outcomes were collected and analysed using the RevMan 5.1 version. Results. Five trials met the inclusion criteria. Compared with DHS, PCCP had similar operation time (95% CI: −26.01~4.05, P = 0.15), length of hospitalization (95% CI: −1.79~1.25, P = 0.73), mortality (95% CI: 0.37~1.02, P = 0.06), incidence of implant-related complications (95% CI: 0.29~1.82, P = 0.49), and reoperation rate (95% CI: 0.41~3.05, P = 0.83). But blood loss (95% CI: −173.84~−4.81, P = 0.04) and transfusion need (95% CI: −0.53~−0.07, P = 0.01) significantly favored the PCCP. Conclusions. The PCCP was associated with reduced blood loss and less transfusion need, but similar to DHS in other respects. Owing to the limitations of this systematic review, more high-quality RCTs are still needed to assess the clinical efficiency of PCCP.